2014
DOI: 10.1016/j.pediatrneurol.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development in Rett Syndrome Deviates From Typical Females

Abstract: Background Rett syndrome is a unique neurodevelopmental disorder, affecting approximately 1 in 10,000 live female births, most experiencing reduced growth. We characterized pubertal trajectories in females with Rett syndrome. We hypothesized that pubertal trajectory deviates from the general female population with early pubertal onset and delayed menarche. Methods Participants were individuals enrolled in the Rett Syndrome Natural History Study with clinical diagnosis of Rett syndrome or mutations in MECP2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
1
28
0
4
Order By: Relevance
“… 65 Longitudinal assessment of pubertal development indicates an increased prevalence of early thelarche and adrenarche but delayed menarche. 66 Difficulties with abnormal tone in this age range typically are characterised by hypotonia evolving to rigidity. 67 68 …”
Section: Resultsmentioning
confidence: 99%
“… 65 Longitudinal assessment of pubertal development indicates an increased prevalence of early thelarche and adrenarche but delayed menarche. 66 Difficulties with abnormal tone in this age range typically are characterised by hypotonia evolving to rigidity. 67 68 …”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that pubertal development in RTT differs from typically developing females 20 . More than 25% may demonstrate premature onset of puberty, the time between the onset of puberty and the onset of menarche is significantly longer than normal (3.9 years in RTT versus 3.0 years in typical females), and the age of menarche is later in RTT (13.0 years) than in typical females (12.5 years).…”
Section: Introductionmentioning
confidence: 98%
“…This patient was in stage 3 of Tanner at 6 years of age, had low gonadotrophins levels and showed an exaggerated response of LH and FSH to stimulation with GnRH (gonadotrophin-releasing hormone). A larger study carried out in 802 women with classic RTT [40], indicated that a significant percentage of patients had premature breast development (Tanner stage 2) and premature appearance of pubic hair (Tanner stage 2). In normal girls, there is usually a synchronic transition between thelarche and pubarche, while the data from that RTT study indicate that in RTT girls there is an inversion of the normal pattern, so that pubarche precedes thelarche by a ratio of 3:1, as happened in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, which does not exclude an abnormal functioning of HPG in RTT girls, could be an increase in the secretion of adrenal androgenic hormones, due to excessive production of corticotropin-releasing hormone (CRH) and ACTH [40], as described in an RTT mouse model [100]. However, plasma adrenal steroids were normal in our patient, while it would be expected that the adrenal precursors of testosterone were in high values, and cortisol in low values, but this did not occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation